2020
DOI: 10.24929/fp.v17i1.1041
|View full text |Cite
|
Sign up to set email alerts
|

Tanaman Biofarmaka; Penyakit Dan Ekonomi

Abstract: Penentuan komoditas unggulan tanaman biofarmaka menjadi fokus utama Kota Medan untuk meningkatkan kualitas kesehatan masyarakat sekaligus menjadi lokomotif ekonomi berkelanjutan. Metode penelitian ini menggunakan metode LQ dan SS, IJAH Analytics dan Studi Pustaka (library research). Hasil analisis melalui metode LQ ditetapkan 3 komoditas tanaman biofarmaka Kota Medan dengan pertumbuhan yang berbeda dan mampu bersaing dengan berbagai komoditas sejenis daerah lain. Pengunaan IJAH Analytics membuktikan komoditas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Establishing a standard profile for microbiota-targeted therapies creates a substantial metabolic impactproof host-microbiome intermediary to identify the 'at-risk' vulnerable group(s). While synbiotics, prebiotics, probiotics, and facilitated microbiota transfer (FMT) have been discovered as treatment regimens that need thorough assessments, 85,86 providing early intervention to susceptible populations, a recent study has also revealed that microbiome transplantation is an effective diabetes prevention measure, showing the need for future studies along this line as well. 87…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Establishing a standard profile for microbiota-targeted therapies creates a substantial metabolic impactproof host-microbiome intermediary to identify the 'at-risk' vulnerable group(s). While synbiotics, prebiotics, probiotics, and facilitated microbiota transfer (FMT) have been discovered as treatment regimens that need thorough assessments, 85,86 providing early intervention to susceptible populations, a recent study has also revealed that microbiome transplantation is an effective diabetes prevention measure, showing the need for future studies along this line as well. 87…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Types of plants that are commonly used as part of the treatment are Zingiber officinale, Kaempferia galangal, Ammomum cardamomum, and Morinda citrifolia. Derived products from these medicinal plants have the potential to be developed and have economic value [9]. The people of the Lintang Tribe in Talang Baru Village, South Sumatra Province use medicinal plants in a simple way, namely by chopping them, grating them, boiling them, or consuming them directly.…”
Section: Introductionmentioning
confidence: 99%